The first - Applegate, Katherine (Applegate, Katherine. Endling ;, 2020)
Doglike Byx and her companions seek out the truth behind Byx's past and determine whether she is truly the last dairne. As they face numerous threats and dangers, the band uncover a treasonous plot by some of the most powerful species that will threaten all the animals in Nedarra. They soon find themselves the leaders of a rebellion and Byx and Khara must transition from youthful explorers to leaders.